The Lack of Mitochondrial Thioredoxin TRXo1 Affects In Vivo Alternative Oxidase Activity and Carbon Metabolism under Different Light Conditions. (18th July 2019) - Florez-Sarasa, Igor; Obata, Toshihiro; Del-Saz, Nstor Fernndez; Reichheld, Jean-Philippe; Meyer, Etienne H; Rodriguez-Concepcion, Manuel; Ribas-Carbo, Miquel; Fernie, Alisdair R
Abstract: The alternative oxidase (AOX) constitutes a nonphosphorylating pathway of electron transport in the mitochondrial respiratory chain that provides flexibility to energy and carbon primary metabolism. Its activity is regulated in vitro by the mitochondrial thioredoxin (TRX) system which reduces conserved cysteines residues of AOX. However, in vivo evidence for redox regulation of the AOX activity is still scarce. In the present study, the redox state, protein levels and in vivo activity of the AOX in parallel to photosynthetic parameters were determined in Arabidopsis knockout mutants lacking mitochondrial trxo1 under moderate (ML) and high light (HL) conditions, known to induce in vivo AOX activity. In addition, 13 C- and 14 C-labeling experiments together with metabolite profiling were performed to better understand the metabolic coordination between energy and carbon metabolism in the trxo1 mutants. Our results show that the in vivo AOX activity is higher in the trxo1 mutants at ML while the AOX redox state is apparently unaltered. These results suggest that mitochondrial thiol redox systems are responsible for maintaining AOX in its reduced form rather than regulating its activity in vivo . Moreover, the negative regulation of the tricarboxylic acid cycle by the TRX system is coordinated with the increased input of electrons into the AOX pathway. Under HL conditions, while AOX and photosynthesis displayed similar patterns in the mutants, photorespiration is restricted at the level of glycine decarboxylation most likely as a consequence of redox imbalance .